Converging optical micro- and nanospectroscopies via the development of surface science with forensic Shannon’s measure of information applied to environmental applications; Optical Nanospectroscopy; Applications - McMillan N. Norman; Rodriguez (Rodriges) Contreras R. D. Raul David; McMillan D. Douglas; Heaton M. Mark; Hrymak V. Victor; Perry S. Simon; Omanovic-Miklicanin E. Enisa; Pissadakis S. Stavros (2023, 2023)
Title screen